Closed-end Funds vs. Open-end Funds A Literature Review - Li, Wei Wei (2007)
The aim of this dissertation is to summarise the previous literature on the closed-end mutual funds, and critically analyze whether closed-end funds (CEFs) provide superior returns compared to open-end funds (OEFs). Supported by a comprehensive discussion on the advantages offered by CEFs, and an empirical analysis on the performance comparison of 40 pairs of US CEFs and OEFs (from September 2002 to August 2007), my inference is that CEFs offer investors a more attractive return than OEFs do. The fact that majority of CEFs currently trading at a discount to net assets value (NAV), makes CEFs investments attractive with various ways to achieve capital gains and enhanced returns. Many scholars advise that CEFs have advantages over OEFs due to taxation benefit, cost efficiency, CEFs discount/premium, leverage, and liquidity.